Mengupas Peran Bapemperda DPRD Provinsi Jawa Barat Tahun 2025 dalam Perjalanan Perda: dari Inisiasi Hingga Penetapan (International Forum of Researchers and Lecturers, 2025)
The Regional Regulation Formation Agency (Bapemperda) is a legislative body under the Regional People's Representative Council (DPRD) that plays a key role in the creation of regional regulations. This study analyzes the function of the Bapemperda of the West Java Provincial DPRD in 2025 throughout the entire regulation formation process using a qualitative approach. The results show that Bapemperda carries out strategic tasks including the preparation of Propemperda (Regional Regulation Proposals), coordination and harmonization of Draft Regional Regulations (Raperda), monitoring discussions, and evaluating the content of the material. In 2025, Bapemperda established 10 Draft Regional Regulations (Raperda) (3 proposed by the DPRD and 7 proposed by the Governor). Bapemperda functions as a bridge for political communication and quality control of regional regulations. Its effectiveness is influenced by coordination, member professionalism, and consistent application of regulatory principles. Challenges faced include time constraints, complexity of substance, and political dynamics. The study recommends strengthening institutional capacity and optimizing the documentation system to support good governance.